ISLAMIC MONEY INSTEAD IMPLICATIONS BASED ON MACROECONOMIC AND SOCIAL VALUE VARIABLES IN INDONESIA - Eva Misfah Bayuni; Muhammad Yunus; Mujahid Mujahid; Shifa Nurul Fadhilah; Yusuf Azis Yusrizal; Silvani Fauziyyah Adilla; Mujahid Al Haq (Univeristas Islam Bandung, 2021)
The purpose of this research is to find out the implications of Islamic Money Instead based on macroeconomic and social variables value in Indonesia. The used data is secondary data of 2010-2019 time series. The method of this research is using Vector Autoregressive and Vector Error Correction Model (VECM). E-views 9 program is used for processing data. The result of this research indicates that there are implications for a variety of Islamic Money Instead in Indonesia based on macroeconomic and social value variables in Indonesia on 1st model. GDP and inflation as macroeconomic variable have positive implication for Islamic Money Instead, meanwhile the exchange rate variable has negative implication on it. On 2nd model there are implications for Islamic Money Instead based on macroeconomic variable. GDP and inflation have positive implication and greater value than the 1st model. While the exchange rate has negative implication and has not a response for Islamic Money Instead shock. Furthermore, the 3rd model indicates that there is positive implication based on social value variable not only for zakat but also infaq shadaqah